Produção e qualidade do inhame sob adubação nitrogenada e tipos de tutoramento - Bertino, Antonio Missiemario Pereira (2017)
In the cultivation of the yam, mineral fertilization mainly with nitrogen and the use of tutoring are essential practices as an economically viable production target. The work was carried out in the field and laboratory of the Federal University of Paraíba (UFPB), in Areia, PB, from February to December / 2015, as the objective of evaluating the production and the quality of the yam as a function of nitrogen doses and types Of tutoring. The experimental design was randomized blocks with the treatments distributed in a 5 x 3 factorial scheme, with five nitrogen doses (0, 50, 100, 150, 200 kg ha-1 ) and three types of tutoring (Shapewearing, stick, and without tutor), In four replicates, in plots 40 useful plants. Ten t ha-1 of bovine manure, 120 kg ha-1 of P2O5 and 100 kg ha-1 of K2O were provided in the fertilization of the plantation. In nitrogen fertilization, the nitrogen doses were divided in two equal 60 and 90 days, After planting. The length, mean mass, total and commercial yields of tubers, percentage of tubers with symptoms of nematode attack, percentage of losses, leaf nitrogen, starch and ash contents were evaluated. The largest length of yams was 23.1 cm in the treatment with 128 kg ha-1 of nitrogen and with a stick. The highest average mass of tubers was 1.23 kg in the soil plants with 102 kg ha-1 of nitrogen under espaliering. The total and commercial productivity of the yam were higher in the tutored plants and fertilized with 109 and 125 kg ha-1 nitrogen respectively. The percentage of tubers with nematode symptoms reached up to 40% in the soil with 126 kg ha-1 of nitrogen. The maximum content of starch in yams was 39.2% and ash of 1.36% obtained at the dose of 165 kg ha-1 of nitrogen. Doses of nitrogen between 102 and 165 kg ha-1 promoted increases in the variables evaluated; The steerage with rod provided higher average mass of tubers, total and commercial productivity and foliar N content; The types of tufts did not interfere in the percentage of tubers with symptoms of nematodes and in the contents of starch and ashes in the yams' tubers; The cultivation of the yam depends on the tufting of the plants.